LocoMMotion: a prospective, non-interventional, multinational study of real-life current standards of care in patients with relapsed and/or refractory multiple myeloma - Mateos, Maria-Victoria; Weisel, Katja; De Stefano, Valerio; Goldschmidt, Hartmut; Delforge, Michel; Mohty, Mohamad; Cavo, Michele; Vij, Ravi; Lindsey-Hill, Joanne; Dytfeld, Dominik; Angelucci, Emanuele; Perrot, Aurore; et al. (Leukemia, 2022)
Despite treatment advances, patients with multiple myeloma (MM) often progress through standard drug classes including proteasome inhibitors (PIs), immunomodulatory drugs (IMiDs), and anti-CD38 monoclonal antibodies (mAbs). LocoMMotion (ClinicalTrials.gov identifier: NCT04035226) is the first prospective study of real-life standard of care (SOC) in triple-class exposed (received at least a PI, IMiD, and anti-CD38 mAb) patients with relapsed/refractory MM (RRMM). Patients (N = 248; ECOG performance status of 0–1, ≥3 prior lines of therapy or double refractory to a PI and IMiD) were treated with median 4.0 (range, 1–20) cycles of SOC therapy. Overall response rate was 29.8% (95% CI: 24.2–36.0). Median progression-free survival (PFS) and median overall survival (OS) were 4.6 (95% CI: 3.9–5.6) and 12.4 months (95% CI: 10.3–NE). Treatment-emergent adverse events (TEAEs) were reported in 83.5% of patients (52.8% grade 3/4). Altogether, 107 deaths occurred, due to progressive disease (n = 74), TEAEs (n = 19), and other reasons (n = 14). The 92 varied regimens utilized demonstrate a lack of clear SOC for heavily pretreated, triple-class exposed patients with RRMM in real-world practice and result in poor outcomes. This supports a need for new treatments with novel mechanisms of action.
CRIS-Team Scopus Importer:2023-03-23